2009
DOI: 10.1002/art.27189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term belimumab treatment on b cells in systemic lupus erythematosus: Extension of a phase II, double‐blind, placebo‐controlled, dose‐ranging study

Abstract: Objective. To understand the effects of long-term BLyS inhibition in human systemic lupus erythematosus (SLE).Methods. Seventeen patients with SLE who were enrolled in a clinical trial of belimumab, a BLyS-specific inhibitor, plus standard of care therapy were studied. Phenotypic analysis of lymphocytes was performed using flow cytometry. Circulating antibody-secreting cells were enumerated using enzyme-linked immunospot assay. Serum was analyzed by enzyme-linked immunosorbent assay using an antibody that reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
148
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 206 publications
(191 citation statements)
references
References 51 publications
31
148
2
10
Order By: Relevance
“…The results presented are consistent with those of a small 2‐year study that investigated the effects of belimumab treatment on levels of B cell subsets 29. Over the duration of the study, there was a decrease in levels for the majority of B cell subsets, but no subsets were completely depleted.…”
Section: Discussionsupporting
confidence: 86%
“…The results presented are consistent with those of a small 2‐year study that investigated the effects of belimumab treatment on levels of B cell subsets 29. Over the duration of the study, there was a decrease in levels for the majority of B cell subsets, but no subsets were completely depleted.…”
Section: Discussionsupporting
confidence: 86%
“…54 Early phase trials with belimumab in patients with SLE showed efficacy in reducing levels of peripheral B cell but have yet to show this B-cell depletion translates into serologic (antibody levels) or clinical (lupus activity scores or, in patients with lupus nephritis, markers of renal function) improvements. [55][56][57] In case reports from Europe, adrenocorticotropic hormone (ACTH) shows promising results in patients with nephrotic syndrome of various etiologies, including membranous nephropathy, membranoproliferative glomerulonephritis, minimal change disease, and focal segmental glomerulosclerosis. 58,59 In a randomized trial in idiopathic membranous nephropathy conducted by Ponticelli et al, 60 ACTH and cyclophosphamide achieved equal rates of disease remission.…”
Section: Newer Agents For Lupus Nephritis Will Be Tested In Combinatimentioning
confidence: 99%
“…The majority of clinical studies in emerging biologic therapies have not addressed the issue of variable clinical response in different ethnic groups. Of note, belimumab was found to be less efficacious in African American patients in phase III clinical trials (Wallace et al, 2009) (Jacobi et al, 2010). Several of the studies of emerging therapeutic strategies described in this chapter, while encouraging, have targeted SLE disease manifestations in general rather than focusing on outcomes in lupus nephritis.…”
Section: Resultsmentioning
confidence: 99%
“…Belimumab was approved by the FDA for treatment of SLE in March 2011, the first lupus drug to be approved since hydroxychloroquine and corticosteroids were approved in 1955. The safety and effectiveness of belimumab was demonstrated in two clinical trials (BLISS-52, and BLISS-76) that randomized a total of 1684 patients to receive either belimumab or placebo in combination with standard therapy (Wallace et al, 2009) (Jacobi et al, 2010). Treatment with belimumab plus standard therapy reduced disease activity and steroid use.…”
Section: Belimumabmentioning
confidence: 99%